A real-time biomechanical feedback system for training rowers - Page, P.; Hawkins, D. (2001)
Average static joint position errors ranged from 0.2 cm to -2.5 cm, with a typical joint location error being 1 cm. Average dynamic joint errors ranged from ±0.1 cm to -4.4 cm, with typical errors on the order of ±1 cm. Joint position errors were more pronounced at the extremes of the stroke. Errors in joint positions resulted in average knee and hip joint angle errors of 9.6° and 5.8°, respectively. Additionally, the average handle horizontal velocity error during the drive phase was -1.8%. Figure 2 provides a visual comparison of the effect that the typical errors have on the RowTrainer stick figure (compared to videography). Two anthropometric data.experienced rowing coaches evaluated the system and concluded that the accuracy was sufficient to provide beneficial feedback.